Evaluating and implementing an opportunity for diversity and inclusion in case-based learning - Bowden, Sylvie; Law, Marcus; Kurabi, Bochra; Naguib, Mariam; Klostermann, Natalie; Freeman, Sarah; Berditchevskaia, Inna; Balbaa, Amira; Kirubarajan, Abirami; Lazor, Jana (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale, 2021)
Implication Statement: Problem-based learning (PBL) and case-based learning (CBL) often mention social identities only if this information is directly relevant to diagnosis, which can inadvertently perpetuate stereotypes in trainee learning. Using a student-developed resource entitled “Portraying Social Identities in Medical Curriculum: A Primer,” we analyzed cases for social identities, identified gaps, and proposed changes, including use of a validated name bank to reflect diversity as represented by local census data. Through this innovation, suggestions were provided to represent the social determinants of health in CBL cases. Other medical schools can use our innovation to improve the social diversity of their medical curriculums.